The Shanghai factor - McCarry, Charles (Grove Press, 2013)
An American spy in China. Name: Unknown. Status: Sleeper. Just when he thought life had settled into a pleasant routine, he is called back to Washington. His assignment: go undercover as the American ambassador for a massive Chinese multinational conglomerate, and learn the secrets of their powerful CEO Chen Qi, whom HQ believes to be a front man for the nearly uncrackable Chinese Intelligence, known as the Guoanbu.